Hemophagocytic Lymphohistiocytosis Associated with Respiratory Syncytial Virus Infection in an Immunocompetent Elderly Patient - Kamel, Ralph; Sharma, Rubal; Asti, Divya; Gill, Arshpal; Skaradinskiy, Yevgeniy (Case Reports in Hematology, 2020)
Hemophagocytic lymphohistiocytosis is a serious and potentially fatal disorder characterized by excessive immune system activation. The disorder is diagnosed mainly based on laboratory, clinical, and pathologic criteria. The spectrum comprises hereditary or “primary” HLH that comprises genetically heterogeneous conditions, occurring during childhood. The secondary form presents later in life and is associated with several conditions mainly malignancy, autoimmune diseases, viral or bacterial infections, and hematological diseases. We present the case of an 80-year-old female patient who initially presented with an acute viral syndrome secondary to respiratory syncytial virus. The hospital course was complicated by disseminated intravascular coagulation and shock with multiorgan failure. Extensive workup revealed that several of the criteria for hemophagocytic lymphohistiocytosis were met. A review of literature fails to identify cases of hemophagocytic lymphohistiocytosis associated with respiratory syncytial virus in immunocompetent adults. This case report provides further insight on RSV as a possible etiologic agent associated with HLH and the importance of early recognition of this fatal disorder in RSV-positive patients who show unpredictable clinical decompensation.